Risk Based in Lieu of Time Based Inspection to Improve Cost Effectiveness for Offsahore Platform in Indonesia Oil and Gas Industry - Gumilang, Fentarie; Tjendrasa, Kin (The Indonesian Journal of Business Administration, 2017)
Abstract- This paper addresses to provides an overview of offshore platform inspections in Indonesia that were previously using time-based to be replaced with risk-based inspections. By Indonesian regulation every platform should be inspected at a time based inspection interval. There are three levels of inspection that were determined by the Indonesian authority, namely minor, major, and complete inspections. Before the risk based method was implemented, the scope and the interval of these inspections were determined by the Indonesian authority by using a time-based approach, with a cycle of 1-year, 2-year, and 4-year for the minor, major, and complete inspection respectively. As underwater inspections are very costly, the risk based underwater inspection (RBUI) analysis is performed to obtain the most efficiency way of carrying out the inspections. Risk based inspection use a mix of qualitative and quantitative analyses. A qualitative analysis is used in the consequences of failure (CoF) factor calculation, and a quantitative analysis is used in the probability of failure (PoF) calculation both of them are used to determine the risk of the platform. The decision making strategy are based on the comparison between time based inspection and risk based inspection from the cost of inspection point of views. The net present value was used to compare between time based inspection cost and risk based underwater inspection cost. Based on the analysis, the cost reduction for a platform on average would reduce by half of the amount projected cost of inspection by implementing the risk based underwater inspection. SWOT analysis and SWOT matrix are used to determine what strategic needs to be done by Indonesian government in implementing risk based inspection to any offshore platform in Indonesia. One of the things that need to be done is to make a regulation as the legal basis for implementing the risk based underwater inspection in Indonesia.Keywords: offshore platform, time based inspection, risk based inspection, net present value, SWOT analysis.